2015
DOI: 10.1109/lmwc.2014.2382655
|View full text |Cite
|
Sign up to set email alerts
|

A 275 GHz Active Vector-Sum Phase Shifter

Abstract: Terahertz vector-sum phase shifters capable of 360 phase control over the frequency range of 240 to 310 GHz are presented. Because the impedance mismatch of the variable-gain amplifiers employed in the phase shifter determines the flatness of the offset phases, a new broadband VGA design with its input and output impedances unaffected by dc bias is introduced. The measured results on the phase shifter fabricated using 0.25 m InP HBT technology show incremental phase shifts of 45 with an average RMS offset phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…At 110 GHz, McPherson et al [48] demonstrated an electronically tunable monolithic microwave integrated circuit (MMIC) in-phase/quadrature-phase (IQ) vector modulator, demonstrating 64-quaternary amplitude modulation (64-QAM) digital modulation directly at the carrier frequency, intended for implementing miniature softwarecontrolled transmitters. Recently, a 275-GHz MMIC phase shifter was reported by Quan et al [49], demonstrating a 360° phase shifter with 13-dB insertion loss over the 240-310-GHz frequency range. These MMIC solutions inherently suffer from high insertion loss and limited power handling capability [50], which may be critical factors for some applications.…”
Section: T U Na Ble T H Z Componen Tsmentioning
confidence: 99%
“…At 110 GHz, McPherson et al [48] demonstrated an electronically tunable monolithic microwave integrated circuit (MMIC) in-phase/quadrature-phase (IQ) vector modulator, demonstrating 64-quaternary amplitude modulation (64-QAM) digital modulation directly at the carrier frequency, intended for implementing miniature softwarecontrolled transmitters. Recently, a 275-GHz MMIC phase shifter was reported by Quan et al [49], demonstrating a 360° phase shifter with 13-dB insertion loss over the 240-310-GHz frequency range. These MMIC solutions inherently suffer from high insertion loss and limited power handling capability [50], which may be critical factors for some applications.…”
Section: T U Na Ble T H Z Componen Tsmentioning
confidence: 99%
“…Design advances over the past decade have led to significant improvements in the fractional bandwidth of the phase shifters and a reduction in the footprint area of the chips. MMIC phase shifters covering the full 360°using different techniques, such as delay lines [1], [2], signal reflection [3], highpass/low-pass networks [4], all-pass networks [5], and vector summation [6]- [12].…”
Section: Introductionmentioning
confidence: 99%